Arrhythmias in Cardiac Sarcoidosis Bench to Bedside: A Case-Based Review. (February 2021) - Rosenfeld, Lynda E.; Chung, Mina K.; Harding, Clifford V.; Spagnolo, Paolo; Grunewald, Johan; Appelbaum, Jason; Sauer, William H.; Culver, Daniel A.; Joglar, Jose A.; Lin, Ben A.; Jellis, Christine L.; Dickfeld, Timm-Michael; et al.
Abstract : Cardiac sarcoidosis is a component of an often multiorgan granulomatous disease of still uncertain cause. It is being recognized with increasing frequency, mainly as the result of heightened awareness and new diagnostic tests, specifically cardiac magnetic resonance imaging and 18 F-fluorodeoxyglucose positron emission tomography scans. The purpose of this case-based review is to highlight the potentially life-saving importance of making the early diagnosis of cardiac sarcoidosis using these new tools and to provide a framework for the optimal care of patients with this disease. We will review disease mechanisms as currently understood, associated arrhythmias including conduction abnormalities, and atrial and ventricular tachyarrhythmias, guideline-directed diagnostic criteria, screening of patients with extracardiac sarcoidosis, and the use of pacemakers and defibrillators in this setting. Treatment options, including those related to heart failure, and those which may help clarify disease mechanisms are included. Abstract : Supplemental Digital Content is available in the text.